Sowing GM Crops: Populating Bioethics in the Malaysian Biosafety ACT 2007 Through Public Participation - Siti Hafsyah Idris (Yuridika, 2019)
The bioethical issue is one of the concerns on genetically modified (GM) crops. One of the features to acknowledge this bioethical issue is through public participation. Through public participation, any concerns relating to the application and the release of GM crops could be integrated in the biosafety decision making process. The role of public participation is essential as it is a foundation of responsible democratic governance. It advocates public consultations by creating opportunities for transparency, informed and representative decision-making processes. This paper appraises the provision on public participation in the Malaysian Biosafety Act 2007 as to the extent to which bioethical issues could be integrated in the biosafety decision making process. The paper also proposes suggestions on good governance of public participation based on the relevant international legal agreements so that it is properly enforced and serves the desired objective of Biosafety Act 2007.